The diverse role of miR‐31 in regulating cancer associated phenotypes. Issue 12 (2nd September 2013) - Laurila, Eeva M.; Kallioniemi, Anne
<x xml:space="preserve">Abstract</x> In the past 10 years research on miRNAs has demonstrated their central role in regulating gene expression both in normal and diseased tissue. The expression of miRNAs is widely altered in cancer, leading to abnormal expression of the genes regulated by these miRNAs, and subsequently alterations in entire molecular networks and pathways. One especially interesting cancer‐related miRNA is miR‐31 which is frequently altered in a large variety of cancers. The functional role of miR‐31 is extremely complex and miR‐31 can hold both tumor suppressive and oncogenic roles in different tumor types. The phenotype caused by aberrant miR‐31 expression seems to be strongly dependent on the endogenous expression levels. For example, in breast cancer loss of miR‐31 expression is associated with high risk of metastases, whereas in colorectal cancer high miR‐31 expression correlates with advanced disease stage. This review summarizes the complex expression patterns of miR‐31 in human cancers, describes the variable phenotypes caused by altered miR‐31 expression, and highlights the current knowledge on the genes targeted by miR‐31. © 2013 Wiley Periodicals, Inc.